Comparing nanoleakage between class II bulkfill and incremental composite restorations using snowplow technique - Amel M. Ali; Dawlat Mostafa; Amal Sakr; Maha El Tantawi; Hoda Abellatif; Mona A. Elkateb (Elsevier, 2023)
Purpose: To compare the nanoleakage between bulkfill and incremental-fill resin composites in class II slot preparations for primary and permanent teeth restored by the snowplow technique. Materials and Methods: Class II slots were prepared in 32 M (16 exfoliated/extracted primary and 16 permanent molars). Optibond All-InOne self-etching adhesive was applied and cured. A flowable composite, Premise, was then injected into the gingival seat without curing using the snowplow technique. Cavities were restored using Sonicfill/bulkfill or microhybrid Herculite composites. Energy dispersive X-ray spectrometry was used to assess nanoleakage as silver deposition percentages along the axial and cervical walls. Multivariate analysis of variance was used to assess the effect of tooth type (primary and permanent teeth) and placement technique (bulkfill and incremental techniques) on nanoleakage at the axial and cervical walls. Results: Bulkfill restorations had significantly greater nanoleakage than incremental restorations at the cervical walls in primary and permanent molars (mean = 1.21 vs 0.49 in primary molars and 0.76 vs 0.24 in permanent molars). Equivalent results were observed at the axial walls of the restorations (mean = 0.66 vs 0.14 in primary molars and 0.28 vs 0.08 in permanent molars, with a P value of<0.001). Conclusions: Less nanoleakage was observed in class II slot/snowplow resin-composite restorations using the incremental technique compared to bulkfill in both dentitions. However, greater nanoleakage was detected on the cervical walls when compared with the axial walls.